1991
DOI: 10.1007/bf01702926
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenic enterocolitis following treatment with cytosine arabinoside-containing regimens for hematological malignancies: A potentiating role for amsacrine

Abstract: A retrospective clinical study was performed to determine the clinical impact of neutropenic enterocolitis (NE) in adult patients with acute leukemia and non-Hodgkin's lymphoma treated with cytosine arabinoside (Ara-C)-containing regimens. The diagnosis of NE was restricted to conditions with clinical signs of peritonitis, ileus, or intestinal hemorrhage. Forty episodes of NE were noted during 461 Ara-C-containing courses (8.6%) in 36 of 211 patients (17%) over a 6-year period. Clinically, 18 cases of ileus, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
1
11
0
2
Order By: Relevance
“…NEC develops in neutropenic patients due to deep wall infection or intestinal inflammation. The incidence of NEC among the lower GI bleeders in our study was 25% (three cases of 12), which is in agreement with other reports [33,34]. Solitary ulcers of the small or large intestine can result from a wide variety of cause.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…NEC develops in neutropenic patients due to deep wall infection or intestinal inflammation. The incidence of NEC among the lower GI bleeders in our study was 25% (three cases of 12), which is in agreement with other reports [33,34]. Solitary ulcers of the small or large intestine can result from a wide variety of cause.…”
Section: Discussionsupporting
confidence: 82%
“…The main causes of bleeding in the lower GI tract were NEC and solitary ulcers. Previous reports on immunocompromised patients have also found that NEC is a major cause of lower GI bleeding [9,33,34]. NEC develops in neutropenic patients due to deep wall infection or intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Nausea, vomiting and diarrhea are the well-known gastrointestinal side-effects of cytosine arabinoside and the severity of these symptoms is related to both dosage and duration of treatment [2,4,7]. The ulcerations of the mucosae caused by antileukemic chemotherapy drugs, and the blunting of host defenses caused by the underlying disease, the steroids used and the prolonged deep neutropenia are all factors that may contribute to the pathogenesis and to the evolution of the gastrointestinal tract infections and, as described by others, the problem seems to be linked more to the association of drugs (cytarabine and idarubicin) than to a specific agent [4].…”
Section: Discussionmentioning
confidence: 99%
“…It is most often associated with leukemia and lymphoma [1,2]. Rarely, it has been described in patients with solid tumors.…”
Section: Introductionmentioning
confidence: 96%